Tunalı Hilmi Beys views on education - Selman, Tunay KAMER (Academic Journals, 2015)
At the beginning of the 20th century, TunalA± Hilmi Bey, who was not an educator, has played an important part among the harsh debates on education surrounding Turkey. The current study analyzes TunalA± Hilmi Bey’s views on education that is a central point in his life and his sophisticated thoughts. TunalA± Hilmi Bey launched big effort to have social and political reforms, which are crucial to sustain country’s development, not to be remained only in thoughts. He brought forward his views regarding the need for simplification of Turkish language and implementing contemporary reforms in education system during the Young Turks movement period, and he continued these activities during his congressman role in Republican period. TunalA± Hilmi Bey emphasized the importance of girls’ education and considered it as a civic right. Moreover, he provided sensitivity on Turkish language use and urge for not using foreign words in education and in government institutions at the cost of penalties. He suggested services for public education such as “evening schools,” “army of teachers” and “mobile training”. In addition, he also emphasized individual enterprise for schooling besides government investments. He stated that theory in education should be followed by application to support permanency. He emphasized early childhood education and asked for compulsory elementary education for all citizens until the age of 13. TunalA± Hilmi Bey was stubborn to include music and sport lessons in the curriculum and proposed sending students to the West in order to equip them with pedagogical knowledge and to investigate elementary schools Key words: TunalA± Hilmi Bey, education, girls’ education, public education, Turkish language
Keywords: 2. Zero hunger; 4. Education